Dosimetric Evaluation of Commercially Available Flat vs. Self-Produced 3D-Conformal Silicone Boluses for the Head and Neck Region - Pollmann, Stephan; Toussaint, André; Flentje, Michael; Wegener, Sonja; Lewitzki, Victor (Frontiers in Oncology, 2022)
Background Boluses are routinely used in radiotherapy to modify surface doses. Nevertheless, considerable dose discrepancies may occur in some cases due to fit inaccuracy of commercially available standard flat boluses. Moreover, due to the simple geometric design of conventional boluses, also skin areas may be covered that should be spared. With the fused deposition modelling technique (FDM), there is a simple and possibly a cost-effective way to solve these problems in routine clinical practice. This paper presents a procedure of self manufacturing bespoke patient specific silicon boluses and their dosimetric evaluation and fit accuracy, in comparison to standard rectangular commercially available silicon boluses. Methods Individual silicone boluses were individually fabricated to cover the surgical scar region of 25 patients who received adjuvant radiotherapy of head and neck cancer at the University Hospital Würzburg. Dose measurements for individual and commercially available boluses were performed with radiochromic films (EBT3) in the high-dose area (scar) and in the lower-dose area (spared healthy skin) in a crossover study. Bolus-to-skin distances were also determined for both types of bolus. The dosimetric influence of skin to bolus distance was also determined on plate phantom for different field sizes. The trial was performed with the hardware routinely available in every radiotherapy department, with the exception of the 3D printer. Conclusions Using individual boluses, a significant dose reduction can be achieved in the skin areas unintended to receive higher therapeutic dose. For the high dose area, dose is slightly increased by individual boluses compared to conventional boluses. Smaller field size is prone to a larger skin bolus distance effect. This may result in substantial underdosing of relevant treatment volumes. This may be espacially relevant for volumetric intensity modulated arc therapy (VMAT) and intensity modulated radiotherapy (IMRT) techniques with a huge number of smaller fields. The limiting factor in the conformity of individual boluses was the immobilization mask which is first produced, which itself limited tight contact of secondary produced 3D boluses to the mask covered body areas. In this respect, bolus adjustment before mask fabrication should be evaluated in the next step.